2021
DOI: 10.1371/journal.pone.0253592
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum magnesium levels and abdominal aorta calcification in patients with pre-dialysis chronic kidney disease stage 5

Abstract: Background Several studies have revealed the relationship between serum magnesium levels and vascular calcification in chronic kidney disease patients. Despite excellent predictability of abdominal aorta calcification for cardiovascular disease events, the relationship between serum magnesium levels and abdominal aorta calcification, as evaluated by quantitative methods, in pre-dialysis patients remains unclear. This study aimed to determine the abdominal aorta calcification volume using computerized tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Within hemodialysis populations, three RCTs studied the effect of 2 to 6 months of oral Mg supplementation on IMT [ 26 , 29 , 30 ]. A recent systematic review and meta-analysis combining these studies demonstrated a significant improvement of IMT for those treated with oral Mg supplements compared to placebo (weighted mean difference (WMD) −0.18; 95% CI −0.34, −0.01) [ 67 ]. Of note, no studies addressing IMT as outcome parameter investigated the effect of increasing dialysate Mg concentration for those on dialysis or oral Mg supplementation for people with CKD stage 1 to 4.…”
Section: Magnesium Administration To Improve Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Within hemodialysis populations, three RCTs studied the effect of 2 to 6 months of oral Mg supplementation on IMT [ 26 , 29 , 30 ]. A recent systematic review and meta-analysis combining these studies demonstrated a significant improvement of IMT for those treated with oral Mg supplements compared to placebo (weighted mean difference (WMD) −0.18; 95% CI −0.34, −0.01) [ 67 ]. Of note, no studies addressing IMT as outcome parameter investigated the effect of increasing dialysate Mg concentration for those on dialysis or oral Mg supplementation for people with CKD stage 1 to 4.…”
Section: Magnesium Administration To Improve Healthmentioning
confidence: 99%
“…These studies demonstrated that solely Mg carbonate or a combination tablet of Mg/calcium carbonate/acetate is equally effective in controlling phosphate levels compared to a calcium-only-containing phosphate binder and sevelamer [ 23 , 24 , 69 ]. However, a recent systematic review and meta-analysis of oral Mg intervention studies in people treated with hemodialysis did not reveal a significant phosphate-lowering effect of these compounds (WMD −0.36 [95% CI −0.89,0.16]) [ 67 ]. Most likely, the small phosphate-lowering effect through intestinal chelation of dietary phosphate by oral Mg supplementation is negligible compared to the phosphate clearance during hemodialysis.…”
Section: Magnesium Administration To Improve Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding all these risk factors created in the context of CKD, hypomagnesemia is yet another interesting and underappreciated risk factor for cardiovascular mortality. Observational data have shown an association between low serum magnesium concentrations or magnesium intake and the increased risk of atherosclerosis, coronary artery disease, arrhythmias, aortic valve calcification [ 47 , 48 , 49 , 50 ], and heart failure [ 51 ]. Furthermore, low serum magnesium levels were associated with an increased risk of end-stage renal disease associated with high serum phosphate levels in a cohort study, suggesting a strong relationship between magnesium deficiency and the adverse effects of high phosphate levels.…”
Section: Cardiovascular Mortality In Chronic Kidney Diseasementioning
confidence: 99%